2018
DOI: 10.1159/000485026
|View full text |Cite
|
Sign up to set email alerts
|

Taking Warfarin with Heparin Replacement and Direct Oral Anticoagulant Is a Risk Factor for Bleeding after Endoscopic Submucosal Dissection for Early Gastric Cancer

Abstract: Background: Although bleeding after endoscopic submucosal dissection (ESD) for early gastric cancer (EGC) remains problematic, especially in patients taking anticoagulants, there are differing views on the ideal and optimal management for these patients. This study investigated the risk of bleeding after ESD in patients taking anticoagulants. Methods: We enrolled 61 consecutive patients taking anticoagulants (anticoagulant group) and 968 patients taking no antithrombotic agents (non-antithrombotic group) treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 34 publications
(36 reference statements)
0
44
1
Order By: Relevance
“…As shown in Table , many studies have reported the risk factors of bleeding after ESD of gastric lesions . Based on the current research results, the risk factors can be classified into patient‐, tumor‐ and operation‐related factors.…”
Section: Risks Of Bleeding After Gastric Esdmentioning
confidence: 97%
See 4 more Smart Citations
“…As shown in Table , many studies have reported the risk factors of bleeding after ESD of gastric lesions . Based on the current research results, the risk factors can be classified into patient‐, tumor‐ and operation‐related factors.…”
Section: Risks Of Bleeding After Gastric Esdmentioning
confidence: 97%
“…Therefore, it is essential to evaluate the association between bleeding risk and thromboembolism when antithrombotic drugs are being administered. Some studies reported that use of antithrombotic drug was a risk factor for hemorrhage after gastric ESD . Conversely, others showed that antithrombotic drugs did not increase such risk .…”
Section: Risks Of Bleeding After Gastric Esdmentioning
confidence: 99%
See 3 more Smart Citations